Approaches for III/V photonics on Si - Wiesner, Mark; Schulz, W-M; Angelopoulos, E. A.; Burghartz, J. N.; Werner, J.; Oehme, M.; Schulze, J.; Rossbach, R.; Jetter, Michael; Michler, P. (AIP Conference Proceedings, 2011)
We investigated different approaches to overcome difficulties in III/V-on-Si heteroepitaxy, namely growth on compliant substrates and virtual Ge substrates, both realized on top of Si substrates, and in addition, directly on Si. The prospect of this work was the realization of a light emitter on standard Si(100) substrate, capable of being integrated in established industrial processes. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-29
Keywords: III/V heteroepitaxy; MOVPE